Advancing Cancer Care Infrastructure in Cambodia: Summary of the First 100 Patients with Cervical Cancer Treated at the National Cancer Centre - Gardner, Jacob; Eav, Sokha; Rath, Beauta; Bunpa, Poly; Mel, Mora; Ath, Vannyat; Thou, Sarameth; Lim, Oussa; Berchuck, Andrew; Sherertz, Tracy (Asian Pacific Journal of Cancer Biology, 2024)
Background: Cervical cancer is Cambodia’s leading cause of female malignancy in both incidence and mortality. Cambodia’s first dedicated multidisciplinary cancer center, the National Cancer Centre (NCC), opened in January 2018 in Phnom Penh, and serves as the main public referral center for the region. Methods: This cross-sectional study retrospectively reviewed the care experience of the first 100 patients with cervical cancer treated at the NCC to collect demographic, diagnostic, and treatment characteristics. Results: The most common FIGO Stage was IIB (T2bN0M0) (n = 17). Squamous cell carcinoma represented 85% of cases. Definitive-intent therapy was recommended for 65 patients; neoadjuvant chemotherapy followed by external beam radiotherapy (EBRT) & tandem and ovoid (T&O) brachytherapy +/- concurrent cisplatin was the most common treatment regimen (n=23). Thirty-five patients presented with recurrent (n=22) or metastatic (n=13) disease and were treated with salvage/palliative intent; neoadjuvant chemotherapy followed by EBRT +/- concurrent cisplatin was the most common treatment regimen (n=10). Of the patients treated with definitive-intent treatment, 92% were prescribed an EBRT dose of 45 Gy in 25 fractions, and the median prescribed T&O brachytherapy dose was 28 Gy in 4 fractions. Mean cumulative EQD2 HR-CTV D90 dose was 91.8 Gy, or ~69-70 Gy to Point A, depending on planning technique. Follow-up data was limited to 27 patients; of the 14 patients whose follow-up period exceeded 1 year, 13 (93%) were alive and disease-free at their last assessment. Conclusion: With multidisciplinary partnership, the NCC has demonstrated that high quality complex cancer care can be delivered in a resource-constrained setting. This early sample of patients treated for cervical cancer is an initial step towards a better understanding of Cambodia’s patient population and an early snapshot of their cancer care delivery capacity.